2020
DOI: 10.1007/s00068-019-01289-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after treatment of distal radius fractures in the elderly using the IlluminOss® System

Abstract: Purpose Distal radius fractures are very common and account for approximately 17% of all fractures treated. Multiple treatment methods are available to treat these fractures, both operative and nonoperative. This study aimed at evaluating the functional and clinical outcomes after treatment of distal radius fractures with the IlluminOss ® System in adult patients. Methods A retrospective case series was performed in a single-level two-trauma center. All consecutive adult patients with a distal radius fracture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Our technique was the product of previous applications of PDN in the appendicular skeleton. [14][15][16][17] While our selected system was initially only FDA approved as a standalone implant for stabilization of the upper extremity (humerus, radius, and ulna), prior reports from Europe, where PDN is used more routinely in the F I G U R E 5 (A) A 72-year-old female with B-cell lymphoma presented with severe acetabular osteolytic metastatic disease with obvious subchondral collapse. (B) and (C) The acetabulum was stabilized with three photodynamic nails (PDN) (1 anterior column and 2 posterior columns), followed by a total hip replacement with screws passing through the PDN.…”
Section: Discussionmentioning
confidence: 99%
“…Our technique was the product of previous applications of PDN in the appendicular skeleton. [14][15][16][17] While our selected system was initially only FDA approved as a standalone implant for stabilization of the upper extremity (humerus, radius, and ulna), prior reports from Europe, where PDN is used more routinely in the F I G U R E 5 (A) A 72-year-old female with B-cell lymphoma presented with severe acetabular osteolytic metastatic disease with obvious subchondral collapse. (B) and (C) The acetabulum was stabilized with three photodynamic nails (PDN) (1 anterior column and 2 posterior columns), followed by a total hip replacement with screws passing through the PDN.…”
Section: Discussionmentioning
confidence: 99%
“…One Level III [ 9 ], Eight Level IV [ 1 , 2 , 5 – 7 , 12 14 ], and three Level V [ 8 , 15 , 16 ] studies reported complications following PBSS. A total of sixty complications were reported (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Radiographic outcomes were reported by six Level IV studies and one Level V study (Table 4 ). Three studies[ 2 , 5 , 12 ] assessing fractures of the distal radius, metacarpals, humerus, and pelvis found complete fracture healing in all patients at 12-month follow up. Similarly, two studies [ 1 , 14 ] found 96% fracture healing among pelvic and humerus fractures, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The IlluminOss PBSS has shown promising clinical results for treatment of a plethora of upper and lower extremity impending, pathologic, and acute fractures 4,6,9,11,13,16,28 . The decision to use the IlluminOss PBSS in this patient was supported by early findings.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of PBSS is vast because authors have reported outcomes in both patients who required prophylactic fixation for impending fractures, as well as operative fixation of acute, traumatic, and/or pathologic extra-articular fractures 7,[11][12][13][14] . Despite early clinical success in Europe, the Illumi-nOss PBSS did not become approved by the US Food and Drug Administration until 2020 4,11 .…”
mentioning
confidence: 99%